ҚАРАҚАЛПАҚСТАНДА ТУРИСТЛИК ХЫЗМЕТ КӨРСЕТИЎШИ МӘМЛЕКЕТЛИК МӘКЕМЕЛЕР ҲӘМ ҚАРАҚАЛПАҚСТАН ТУРИЗМ КОМИТЕТИ ТАРИЙХЫ - Отенов, Нариман Турдымуратович (FAN va JAMIYAT, 2026)
The article examines the activities of state institutions providing tourism services in the Republic of Karakalpakstan, as well as the history of the formation and development of the Karakalpakstan Tourism Committee. The tourism potential of the region and modern prospects for the development of the industry were also discussed.